Auditory working memory mechanisms mediating the relationship between musicianship and auditory stream segregation - Liu, Martha; Arseneau-Bruneau, Isabelle; Farrés Franch, Marcel; Latorre, Marie-Elise; Samuels, Joshua; Issa, Emily; Payumo, Alexandre; Rahman, Nayemur; Loureiro, Naíma; Leung, Tsz Chun Matthew; Nave, Karli M.; von Handorf, Kristi M.; et al. (Frontiers in Psychology, 2025)
This study investigates the interactions between musicianship and two auditory cognitive processes: auditory working memory (AWM) and stream segregation. The primary hypothesis is that AWM could mediate a relationship between musical training and enhanced stream segregation capabilities. Two groups of listeners were tested: the first aimed to establish the relationship between the three variables, and the second aimed to replicate the effect in an independent sample. Music experience history and behavioral data were collected from a total of 145 healthy young adults with normal binaural hearing. The AWM task involved the manipulation of tonal patterns in working memory, while the Music-in-Noise Task (MINT) measured stream segregation abilities in a tonal context. The MINT expands measurements beyond traditional Speech-in-Noise assessments by capturing auditory subskills (rhythm, visual, spatial attention, prediction) relevant to stream segregation. Our results showed that musical training is associated with enhanced AWM and MINT performance and that this effect is replicable across independent samples. Moreover, we found in both samples that the enhancement of stream segregation was largely mediated by AWM capacity. The results suggest that musical training and/or aptitude enhances stream segregation by way of improved AWM capacity.